Discourse on the Disbandment of Front Pembela Islam and Renegotiation of Democratic Ideas - Nuryana, Arief; Narwaya, St. Tri Guntur (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
The Indonesian government, through a joint decision of the Minister of Home Affairs, the Minister of Law and Human Rights, the Minister of Communication and Information, the Attorney General of the Republic of Indonesia, the Chief of the Indonesian National Police, and the Head of the National Counter-Terrorism Agency have designated the mass organization the Front Pembela Islam (FPI) as a prohibited organization. This decision has given rise to polemics and various discourse debates. The pros and cons of more robust public discourse are related to the problem of the idea of ​​democracy. Some of the narratives agree because FPI has been considered a threat to democracy. Some other articulations refuse because this decision violates the principles of democracy itself. Through the perspective of Ernesto Laclau and Chantal Mouffe's Critical Discourse analysis, this paper attempts to examine the polemic of the discourse on the disbandment of the FPI and the renegotiation of the idea of ​​democracy. Several essential notes were found: First, the plurality of responses to the discourse on the disbandment of the FPI was caused by the various articulation formations concerning the preference for the meaning of democracy. Second, democracy is an empty sign whose meaning will always be constantly negotiated. Third, the disbandment of FPI can be read as a concrete form of the ambivalence of democracy, which, in principle, is always fluid to be articulated by any narrative configuration. To cite this article (7th APA style): Nuryana, A. & Narwaya, S. T. G. (2023). Discourse on the disbandment of Front Pembela Islam and renegotiation of democratic ideas. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(1), 60-71. https://doi.org/10.36782/jcs.v13i1.2402